THU0728-HPR A mixed methods study of a group physiotherapy programme incorporating exercise and education in fibromyalgia patients. (12th June 2018) - Parreira, J.; Caeiro, C.; Fernandes, R.; Cruz, E.
Abstract : Background: Research on non-pharmacological treatments for fibromyalgia patients has demonstrated that exercise and education have positive effects on pain and disability 1 . However, the traditional approach of studying treatment effectiveness based exclusively on quantitative measures has been questioned. There is growing recognition of the importance of integrating patients` perspectives into clinical research. Outcome measures focused on patients` perceptions of improvement have been increasingly used, however they do not offer expanded definitions of what constitutes a "successful" outcome 2 . The further exploration of patients` perspectives about treatment benefits may contribute to the development of treatments that better match patients` needs. Objectives: The aim of this study was twofold: firstly, to examine the effectiveness of a group physiotherapy programme (incorporating exercise and education) on pain intensity, disability and global impression of change in fibromyalgia patients; and, to explore how patients, who achieved success in pain and/or disability (according to the score from the Patient Global Impression of Change Scale - PGIC), understand and make sense of the results. Methods: A sequential explanatory mixed methods approach, combining quantitative (1 st phase) and qualitative methods (2nd phase), was carried out. In the 1 st phase, the participants underwent an 8 week (3 times weekly) standardised group programme. Participants were assessed at baseline, 4 and 8 weeks later. Outcome measures included the Numeric Pain Rating Scale (NPRS), the Revised Fibromyalgia Impact Questionnaire (FIQR) and the PGIC. Participants who had scored ≥5 in the PGIC were invited to participate in a focus group. In the 2nd phase, 2 focus groups meetings were carried out to collect data. A semi-structured interview schedule was used and the sessions were audiotaped and transcribed verbatim. Results: Thirty-seven participants (females; 49.3±10.2 years) completed the 1 st phase. Analysis using SPSS revealed statistically significant improvements on pain intensity (mean SD change:−1.38±2.363, p=0.001) and disability (−21.577±21.02, p<0.001). In what concerns to participants` impression of change, 26 participants (70.3%) perceived substantial improvements on pain and disability (PGIC ≥5). From these, 12 accepted to participate in the focus groups. The qualitative analysis indicated that "doing more daily-life activities" and "taking less medication" were identified as the main reasons for the participants` improvements. According to these participants, the knowledge about strategies for self-management played a key role in their success. Conclusions: The combination of data from both phases provided detailed information about the participants` perceptions regarding the key elements for achieving success with a physiotherapy programme. Further research on patients` perspectives regarding treatment effectiveness is recommended since it may contribute to the design of more effective and patient-centred treatments. References: [1] Macfarlane GJ, Kronisch C, Dean LE, et al. EULAR revised recommendations for the management of fibromyalgia. Annals of the Rheumatic Diseases2017;76:318–328. [2] Evans R, et al. "'I Know It's Changed': a Mixed-Methods Study of the Meaning of Global Perceived Effect in Chronic Neck Pain Patients. European Spine Journal2014;23(4):888–97. Disclosure of Interest: None declared